ANALISIS LIVING HADIS TERHADAP FENOMENA PENUNDAAN DISTRIBUSI ZAKAT FITRAH DI DESA RAO-RAO DOLOK KECAMATAN SOSA KABUPATEN PADANG LAWAS - Nurjannah Nasution; Sulaiman Muhammad Amir (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
Normatively, the Hadith of Prophet Muhammad Saw., commands that Zakat al-Fitr be distribution before the Eid al-Fitr prayer. However, the sosiological reality in Rao-Rao Dolok Village reveals that distribution by amil consistently delayed past this limit. This study aims to analyze this delayed distribution through the perspective of Living Hadith studies. A descriptive qualitative approach was employed using textual and contextual living hadith methods. Primary data were gathered through interviews with amil, muzakki and mustahiq, alongside village zakat records triangulation. The novelty lies in dissecting the sociological dialectic of community interactions (living hadith practices) toward managerial constraints at the village level, rather than merely examining the textual laws of zakat delay. The findings indicate that the delay is caused by managerial and sosiological constraints instead of theological factors. Key obstacles include muzakki piling up payments on takbiran,night, limited amil personnel, and transportation challenges using “becak” for door to door delivery. In hadith law, delaying distribution without a valid sharia excuse (uzur syar’i) shifts the zakat status implies the urgent need to restructure payment timing by village amil and the reinforce theological education by local religious leaders to align distribution management with the maqashid of the Prophet’s Hadith.